The impact of the threat of terrorism on U.S. District Court decisions during wartime - Tauber, Steven C. (Terrorism and political violence, 2017)
Federal courts are key actors in the U.S. government’s fight against terrorism because they adjudicate cases based on the USA PATRIOT Act, and accordingly make national security policy. We examine the extent that the terror threat influences judicial decisions in a dataset of 111 USA PATRIOT Act cases decided in the U.S. District Courts from 2001 through 2013, while controlling for other judicial decision-making variables. The results demonstrate that when a case involves a heightened terror threat, federal judges are more likely to defer to the government. Some key control variables are also significant.